APPLICATION OF INTRAGASTRIC BALLOONS IN OBESITY TREATMENT - Durmishi, Ymer (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Obesity is a complex, chronic, metabolic disease characterized by excessive accumulation of adipose tissue in the body and numerous side effects on health. Endoscopic bariatric therapy (EBT) is just one method of treating obesity. Of the many EBT devices, intragastric balloons (IGBs), which take up some space in the stomach, are the most widely used in clinical practice. The aim of this study was to demonstrate the effectiveness of the use of IGB in the treatment of obesity and to compare the results of the use of two different IGBs, Spatz and Edd-ball. The study included 30 overweight patients with BMI (body mass index) between 25 and 40 kg /m 2 , treated with IGB application. All patients were monitored for a period of 6 months from IGB placement until its removal. Number of kilograms lost 6 months after IGB application, BMI change, the presence of comorbidities before and after the intervention, complications durig the intervention and patient satisfaction with the success of the procedure were analyzed. A comparison was also made between the results obtained with the two different types of IGB (Spatz and Edd-ball). The average weight loss 6 months after IGB application was 15.3 kg. Comparison of BMI values ​​before and 6 months after the intervention showed a statistically significant decrease in BMI after the intervention (p = 0.00). The comparison of the lost kilograms in relation to the type of IGB applied did not show a statistically significant difference between the two types of IGB used. Changes in comorbidities after the intervention did not show statistically significant differences.Despite the limitations of this study, which was performed on a small number of patients, the use of IGB has proven to be an effective method of weight loss. No serious complications or fatalities were reported during the procedure. Keywords : obesity, intragastric balloon, therapy, endoscopy. https://doi.org/10.55302/JMS2143149d